Field Adaptation for Watermelon Cultivation under Shallow Ground Water Table in Tidal Lowland Reclamation Area - Momon Sodik Imanudin; Satria JP; Bakri Bakri; M. Edi Armanto (Center for Journal Management and Publication, 2020)
Â Agriculture productivity of tidal lowland reclamation areas in South Sumatra is still low. It leads to the increasing of agricultural land conversion into plantation areas. Controlling the water table is the main factor in the tidal lowlands; this research aimed to develop micro drainage system in tertiary block for controlling water table under wet condition. Watermelon was used as a crop indicator and planted in mid- March 2015. The location of the research was in a tidal lowland agriculture with land typology B, where the tide can only be as irrigation during the rainy season. The method of this research was surveying and monitoring. Groundwater observation, measurement value hydraulic conductivity and land drainage applications were included in the field activities. The design of land drainage used an intensive shallow drainage concept; the effect of the depth of the water table to water status was evaluated by the UPFLOW model. A micro drainage on tertiary block was used by 8 m drain spacing, with channel depth of 20 cm. The results showed that the tertiary gate operation was maximum drainage option. The water table depth was 25 cm in soil depth.The watermelon crops grew well and production reached 20 t ha-1.Â Â